The Effect Of Economic Learning Outcomes And Economic Expectations On The Economic Independence Of Generation Z Individuals Through Moderation Of Financial Intelligence : Study On Economic Education Students At Makassar State University - Sachrir, Muh Irshan; Wahjoedi, Wahjoedi; Mukhlis, Imam (PT. BATARI EDU CALYA, 2023)
Technological advances and the rapid flow of information through the internet have affected the lives of generation Z, one of which is the change in consumptive attitudes that are increasing. However, some of Generation Z still have a very low awareness of digital literacy. The results of economic learning are seen to be able to determine the economic expectations of generation Z and be able to foster financial intelligence in economic independence. This study aims to investigate the effect of economic learning outcomes and economic expectations on Economic Independence in generation Z, with financial intelligence as a moderating factor. This type of research is quantitative research with a descriptive approach and uses a questionnaire as a data source. The sampling method used was Proportionate Stratified Random Sampling, and the number of samples obtained was 77 students at Makassar State University. The data analysis used in this study is the PLS method through SmartPLS software and inferential statistical analysis using the warpPLS version 4.0 program. The results showed that economic expectations and financial intelligence have a positive and significant influence on Economic Independence, while economic learning outcomes do not have a significant effect. The findings provide important insights into the factors that influence generation Z's economic independence and the implications for the development of economic literacy